2006
DOI: 10.1080/14992020500429518
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear hearing aid fittings – 1. Patterns of benefit

Abstract: We evaluated the benefits of fast-acting WDRC, slow-acting AVC, and linear reference fittings for speech intelligibility and reported disability, in a within-subject within-device masked crossover design on 50 listeners with SNHL. Five hearing aid fittings were implemented having two compression channels and seven frequency bands. Each listener sequentially experienced each fitting for a 10-week period. Outcome measures included speech intelligibility under diverse conditions and self-reported disability. At a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 39 publications
5
116
1
Order By: Relevance
“…Since the 2003 Eriksholm consensus article was published, cognition has been implicated in a growing body of research investigating benefits from hearing aids. This research suggests that different types of signal processing algorithms seem to provide different mixtures of (dis)advantages to patients, according to their cognitive capacity (e.g., Davis 2003;Gatehouse et al 2003Gatehouse et al , 2006aHumes 2003Humes , 2007Humes & Wilson 2003;Lunner 2003;Humes & Floyd 2005;Foo et al 2007;Lunner & Sundewall-Thorén 2007;Rudner et al 2008Rudner et al , 2009Rudner et al , 2011Arehart et al 2013;Ng et al 2013Ng et al , 2015Neher 2014;Souza et al 2015;Ohlenforst et al 2016).…”
Section: Clinical Relevance Of Auditory-cognitive Interactions and LImentioning
confidence: 99%
“…Since the 2003 Eriksholm consensus article was published, cognition has been implicated in a growing body of research investigating benefits from hearing aids. This research suggests that different types of signal processing algorithms seem to provide different mixtures of (dis)advantages to patients, according to their cognitive capacity (e.g., Davis 2003;Gatehouse et al 2003Gatehouse et al , 2006aHumes 2003Humes , 2007Humes & Wilson 2003;Lunner 2003;Humes & Floyd 2005;Foo et al 2007;Lunner & Sundewall-Thorén 2007;Rudner et al 2008Rudner et al , 2009Rudner et al , 2011Arehart et al 2013;Ng et al 2013Ng et al , 2015Neher 2014;Souza et al 2015;Ohlenforst et al 2016).…”
Section: Clinical Relevance Of Auditory-cognitive Interactions and LImentioning
confidence: 99%
“…In two separate reviews, analyzing twenty studies (Akeroyd, 2008) and twenty-one studies (Besser et al, 2013), it was found that in most of the studies the speech recognition in noise was most reliably predicted by WMC as measured by the reading span test (Daneman & Carpenter, 1980;Rönnberg, Arlinger, Lyxell & Kinnefors, 1989). In the domain of hearing aids, it has been shown that WMC correlates with aided speech recognition in noise performance (Foo, Rudner, Rönnberg & Lunner, 2007;Gatehouse, Naylor & Elberling, 2003, 2006a, 2006bLunner, 2003, Lunner andSundewall-Thorén, 2007). The ability to derive benefit from digital signal processing algorithms in hearing aids is also associated with WMC (Arehart et al, 2013;Cox & Xu, 2010;Lunner, 2003;Lunner and Sundewall-Thorén, 2007;Rudner, Foo, SundewallThorén, Lunner & Rönnberg, 2008;Rudner, Foo, Lunner & Rönnberg, 2009;.…”
Section: Working Memorymentioning
confidence: 99%
“…Each dimension was assessed in relation to four pre specified listening situations (if they occur in the participant's life and cause them difficulty) with the option of including up to four additional listening situations specified by the respondent. The GHABP has been used with success to examine patterns of benefit in linear and nonlinear hearing aid fittings (Gatehouse et al, 2006a), the effect of counseling on perceived hearing aid benefit (Kemker and Holmes, 2004) and on acclimatisation to the fitting of monaural hearing aids (Munro and Lutman, 2004). The GHABP was administered by the experimenter as a structured interview.…”
Section: Self-report Questionnairesmentioning
confidence: 99%